Ferroelectric, Ferroelastic, Piezoelectric, and Dielectric Properties of Lead Zirconate Titanate from –150°C to 350°C - Kaeswurm, Barbara; Schader, Florian; Webber, Kyle Grant (Ceramics International, 2018)
The ferroelectric, ferroelastic, piezoelectric, and dielectric properties of co-doped, soft-type Pb(Zr,Ti)O3 were measured from −150°C to 350 °C, highlighting the importance of temperature and defects on the electromechanical response. Small signal piezoelectric measurements revealed a linear increase with increasing temperatures below 0 °C, followed by a maximum at approximately 50 °C. The low temperature properties correspond well to observed changes in the large-field response during the application of an external electrical and mechanical field. The results illustrate the importance of understanding phase boundary effects in order to determine a useable temperature range and to tailor future lead free piezoelectric materials for cryogenic electromechanical applications.
Keywords: ferroelasticity; ferroelectricity; phase boundary; piezoelectricity